On the interim pricing of unbundled local loop - Madden, Gary; Bohlin, E.; Ahmad, Hasnat (Communication Economics and Electronic Markets Research Centre, 2011)
This study continues the analysis of Sidak and Singer (2002) by examining OECD fully unbundled and line sharing monthly wholesale prices for 2002–2008. These data are analysed within an unbalanced panel model context. Comparison of the series reveal fully unbundled prices are higher those for line sharing, the decline of fully unbundled prices is the faster. Further, while both series are reasonably well explained by the models, the importance of individual arguments is different. In particular, national population and degree of urbanization are important for fully unbundled prices, while population density and the wage index are important for line sharing prices. Finally, both price series are subject to increasingly rapid decline value, although the patterns are somewhat distinct. An implication of this finding is that initial prices are truly transitory, and that markets quickly correct ‘bad’ mandated initial values.